PENGARUH PEMBERIAN KOMUNIKASI INTERPERSONAL TERHADAP PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG MENSTRUASI DAN DYSMENORRHOE DI SMA MUHAMMADIYAH 2 PALEMBANG TAHUN 2008 - Sulaiman Sulaiman (Publikasi Penelitian Terapan dan Kebijakan, 2020)
When a woman menstruates for first time, moment that's him has passed adult spandrel. Vital organ as a woman have “matured". Ironically, many “small girl" are muzziness, surprise and have no idea, when for first time see coherent blood in her underwear. Menstruates cycle range from 21-40 day, and only about 10-15% women owning cycle 28 day. Problem of which is often faced by women when menstruating arriving is menstrual moment pain in bone or dysmenorrhoe. Dysmenorrhoe often happened, possibility more than 50% natural women and 15% among others experience of super pain in bone. Usually primary dysmenorrhoe arise at teen-age, that is about 2-3 year after first menstruating. Intention of this research is to know influence of interpersonal communications giving to knowledge, action and attitude of girl about menstruating and dysmenorrhoe. Research type was Quasi Experimental by using pre-post test design. Samples are done by random sampling by using sampling random simple technique. Research samples was women student which enlist and active as student in SMA Muhammadiyah 2 Palembang during even semester of school 2007 / 2008 with class criterion 1 and 2 counted 100 samples from 130 totalizing population. Utilized data analysis was Wilcoxon test. Result of data analysis showed there is significant relation between interpersonal communications giving with knowledge of girl about menstruating and dysmenorrhoe where p value < 0,05 (p value= 0,000). Result of data analysis showed that there was significant relation between giving of interpersonal communications with attitude of girl about menstruating and where p value < 0,05 (p value= 0,000). While at attitude of girl about dysmenorrhoe according to result of data analysis showed that there is no significant relation between giving of interpersonal communications with attitude of girl to dysmenorrhoe where p value > 0,05 (p value= 0,269). From result of this research, hence suggestion raised by researcher is to be health institution expected to more impetuous in counseling and pay attention to menstruate and dysmenorrhoe of girls.